Options for transporting Russian gas to Western Europe : a game-theoretic simulation analysis - Christian R. von Hirschhausen; Berit Meinhart; Andreas Chollet; Petra Opitz (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
This paper examines the perspectives of Russian gas exports to Western Europe and the strategic options of the CIS gas transiting countries, namely Ukraine and Belarus. The development of a new transit corridor through Belarus (the Yamal-Europe pipeline), depriving Ukraine of its former monopoly, has modified the situation profoundly. The thrust of the paper is an analysis of the strategies that Ukraine and Belarus may pursue in transiting Russian gas: non-cooperative duopoly, cooperative duopoly, and individual or collective cooperation with Russia. Using a demand function for Western European gas imports from Russia, we estimate prices and quantities for gas transit, the expected profits for Russia, Ukraine, and Belarus, and the resulting import prices for Western Europe. The results indicate that Ukraine suffers a loss of several hundred million USD annually from the market entry of Belarus, Belarus has an incentive to increase its gas transit capacity to at least 56 billion cubic meters, and Russia's profits increase, in particular when it unites its gas sector with Belarus and Ukraine, a strategy pursued by Russia's Gazprom presently. For Western Europe, all scenarios indicate an increase in welfare through the new pipeline, but also an increasing importance of gas imports from Russia.
Keywords: 330; Gasleitungstransport; Transit; Gebühr; Staatliche Preispolitik; Spieltheorie; Theorie; Ukraine; Weißrußland; Erdgas; Export; Rußland; Westeuropa